Ethnomathematics-Based Edutainment: Exploring the Enhancement of Mathematical Reasoning Skills Through Video Games - Novitasari, Dwi; Kertiyani, Ni Made Intan; Wulandari, Nourma Pramestie (JDIME: Journal of Development and Innovation in Mathematics Education, 2024)
This study aims to develop an ethnomathematics-based visual novel game, named "EtnoMath," to enhance students' mathematical reasoning abilities in fraction material. The game was developed in response to students' difficulties in understanding mathematical reasoning concepts, which have led to low learning outcomes. This research employed a Research & Development (R&D) approach using the Alessi & Trollip model, which consists of three stages: planning, design, and development. Expert validation (content and media), practicality analysis, and product effectiveness analysis were conducted as part of the evaluation process. Data collection techniques included validation questionnaires, teacher and student practicality questionnaires, and mathematical reasoning ability tests. The results indicated that "EtnoMath" meets the criteria for being valid, practical, and effective, with a media validity score of 88% (very valid) and a content validity score of 90% (very valid). The practicality level was rated at 84% by teachers and 84% by students (both very practical). Effectiveness analysis, both from individual and classical mastery tests, showed that student mastery exceeded 80% in field trials. Effectiveness testing using a one-sample t-test showed a significant improvement in post-test scores (M = 87.25, p < 0.001) compared to the minimum mastery criterion (KKTP = 80), while a binomial test confirmed that all students exceeded this benchmark (p = 0.000).These findings suggest that "EtnoMath" is effective in enhancing students' mathematical reasoning skills and aligns with modern pedagogical standards. However, the study has limitations, such as a lack of long-term evaluation and adaptation to various user needs. The implications of these findings highlight the need for further development to improve the game's flexibility and expand its application in broader educational contexts.